Impacts of religious semantic priming on an intertemporal discounting task: Response time effects and neural correlates. (August 2016) - Morgan, Jonathan; Clark, Dustin; Tripodis, Yorghos; Halloran, Christopher S.; Minsky, April; Wildman, Wesley J.; Durso, Raymon; McNamara, Patrick
Abstract: The purpose of this study is to test the hypothesis that religious primes would influence intertemporal discounting behaviors in neurotypical older adults, but not in participants with Parkinson's disease (PD). Furthermore, we predicted that this priming effect would be related to functional connectivity within neural networks mediating religious cognition, decision-making, reward valuing, and prospection processes. Contrary to past research with young adults, we found a significant positive relationship between religiosity and discounting rates. Religious semantic primes did not reliably shift individual discounting rates. But religious controls did respond more quickly to intertemporal decisions under the religious priming condition than the neutral condition, compared to response time differences among the participants with PD. Differences in response time were significantly associated with functional connectivity between the nucleus accumbens and various regions, including the left anterior cingulate cortex and Brodmann areas 10 and 46 in the right dorsolateral prefrontal cortex. These results suggest that religious primes influence discounting behavior via dopaminergic meso-limbic and right dorsolateral prefrontal supporting cognitive valuation and prospection processes. Highlights: We investigated the neural underpinnings of the religion/impulsivity relationship. Intertemporal discounting rates were positively correlated with religiosity. Religious semantic primes did not impact intertemporal discounting rates. Religious semantic primes did quicken responses among neurotypical participants. Accelerated responses are predicted by connectivity in the dopaminergic system.